PENGELOLAAN LABORATORIUM BIOLOGI DI SEKOLAH BERTARAF INTERNASIONAL (SBI) (Studi Situs di SMA Negeri Klaten) - Suwarno, Priyo (2011)
The purpose of this study were (1) to describe the characteristics of the procurement of equipment and materials in high school biology laboratory High School 1 Klaten. (2) To describe the characteristic use of biological laboratory in High School 1 Klaten in learning biology. (3) To describe the characteristics of maintenance and repair of biological laboratories in High School 1 Klaten. This type of research is qualitative research. Location of the research conducted in High School 1 Klaten. Data collection technique used observation techniques to participate, an interview or interviews, and documentation. The data analysis technique in this research using descriptive technique with three procedures: (1) data reduction, (2) presentation of data, and (3) the withdrawal of conclusions / verification. The results of this study were (1) Procurement of facilities and infrastructure in high school biology 1 Klaten, planned by the teacher of biology, made be made each year end, is used as a material planning budget revenue and expenditure of schools (School Budget). Planning procurement tool is need for tools and materials the proposal in detail, in addition to the proposed procurement of equipment and raw material procurement in the proposed planned maintenance requirements and repair tools. The process of procurement of facilities and infrastructure in High School 1 Klaten is the result of the evaluation and planning activities and infrastructure facilities. The procurement process involves all elements of the school committee, teachers, and the laboratory. Procurement of purchases made by officers each working unit on suppliers who have obtained a recommendation by the Principal. (2) Use of biological lab facilities and infrastructure in High School 1 Klaten used to support the theory of learning biology by biology teachers in the classroom. Use of biological lab is used by all teachers starting from class X to class XII, with a schedule every day use hours are from I to VII hour. Use of biological lab equipment by students is done by filling out the form of the loan. All use of biology laboratory infrastructure is the responsibility of laboratory staff. (3) Maintenance of biological laboratories performed continuously, periodically, and emergency. Maintenance done on a schedule made by the laboratory. Improved infrastructure and facilities that are lightweight and teachers conducted by the Laboratory, while in case of heavy damage repairs performed by outside contractors, after receiving the starving of the Laboratory.